(untitled) (Research, Society and Development, 2023)
The present work deals with the diagnosis and drug therapies for Abdominal Aortic Aneurysm (AAA) as a way to raise discussions about the safety of patients affected by the disease or the early diagnosis of AAA. It is observed that AAA morbidity is related to lack of care or negligence in health screening (imaging tests) and pharmacological complications. To track more current diagnostic and treatment methods against AAA, we performed an integrative literature review. We selected articles published in the period between 2017 and 2021 in the data bases Latin American and Caribbean Literature in Health Sciences (LILACS), MEDLINE, PUBMED and Scientific Electronic Library Online (SciELΟ). 11 articles were found, which, after using the inclusion and exclusion criteria, left 09 articles selected for analysis of the results. It was possible to observe that early diagnosis and ultrasonographic follow-up of the growth of the aneurysm sac in patients with AAA is important for reducing mortality, especially in the elderly, where rupture can happen by chance. AAA is more prevalent than Thoracic Aortic Aneurysm and the discovery of these cardiovascular diseases is related to the development of image observation technologies (imaging). Surgical interventions can be performed, such as the introduction of a stent or endovascular correction. Most commonly used drug therapies for prophylaxis of AAA complications, but not for aneurysm size reduction. Among the medications used, we can mention statins to reduce arterial and hypolipidemic inflammation, antiplatelet agents to improve blood flow and stent maintenance, corticosteroids (inflammatory protection), beta-blockers to reduce cardiac contractility and reduce the risk of internal bleeding. We ratify that there is no scientific evidence that drug therapies help to reduce the size of the AAA. Early screening, use of corrective measures, adherence to pharmacological treatment and monitoring of the aneurysm reduce mortality and promote patient safety.